Dreams and lives in Ottoman Istanbul - Niyazioğlu, Aslı (Routledge, 2017)
Dreams and Lives in Ottoman Istanbul explores biography writing and dream narratives in seventeenth-century Istanbul. It focuses on the prominent biographer 'Aṭā'ī (d. 1637) and with his help shows how learned circles narrated dreams to assess their position in the Ottoman enterprise. This book demonstrates that dreams provided biographers not only with a means to form learned communities in a politically fragile landscape but also with a medium to debate the correct career paths and social networks in late sixteenth and early seventeenth-century Istanbul Introduction – The biographer between this world and the hereafter – Patrons and adversaries – Sufi sheikhs and the very special dead – Father and son – Collection of lives as a well-ordered garden – Ottoman biographers and Sufi lives : an overview – A well-ordered garden : empire, decorum and exclusivity – Gardener at work : ʻAṭā'ī and his sources – From this world to the realm of dreams – Dreams, careers and biographers – Nightmares on the Sufi path – Hereafter in the mirror of dreams – The dead and visits from the hereafter – The living and the dead in seventeenth-century Istanbul – Apparitions and embraces – Dreams and tokens of remembrance – Epilogue
Includes bibliographical references and index
Keywords: ʻAṭā'ī; ʻAṭā Allāh ibn Yaḥyā; Biographers; Biography as a literary form; Dreams in literature